Analysis of risk factors for parenteral nutrition-associated cholestasis in preterm infants: a multicenter observational study - Ya-sen Wang; Wei Shen; Qing Yang; Rong Lin; Li-xia Tang; Rui-miao Bai; Dong Yang; Juan Zhang; Yi-jia Zhang; Wen-ting Yu; Shi-rong Song; Juan Kong; et al. (BMC, 2023)
Abstract Background It is proposed that the development of parenteral nutrition-associated cholestasis (PNAC) was significantly associated with preterm birth, low birth weight, infection, etc.; however, the etiology and pathogenesis of PNAC are not fully understood. Most of the studies examining PNAC-associated risk factors were single-center studies with relatively small sample sizes. Objective To analyze the risk factors associated with PNAC in preterm infants in China. Methods This is a retrospective multicenter observational study. Clinical data on the effect of multiple oil-fat emulsions (soybean oil-medium chain triglycerides-olive oil-fish oil, SMOF) in preterm infants were collected from a prospective multicenter randomized controlled study. A secondary analysis was performed in which preterm infants were divided into the PNAC group and the non-PNAC group based on the PNAC status. Results A total of 465 cases very preterm infants or very low birth weight infants were included in the study in which 81 cases were assigned to the PNAC group and 384 cases were assigned to the non-PNAC group. The PNAC group had a lower mean gestational age, lower mean birth weight, longer duration of invasive and non-invasive mechanical ventilation, a longer duration oxygen support, and longer hospital stay (P < 0.001 for all). The PNAC group had higher respiratory distress syndrome, hemodynamically significant patent ductus arteriosus, necrotizing enterocolitis (NEC) with stage II or higher, surgically treated NEC, late-onset sepsis, metabolic bone disease, and extrauterine growth retardation (EUGR) compared to the non-PNAC group (P < 0.05 for all). In contrast with the non-PNAC group, the PNAC group received a higher maximum dose of amino acids and fat emulsion, more medium/long-chain fatty emulsion, less SMOF, had a longer duration of parenteral nutrition, lower rates of breastfeeding, higher incidence of feeding intolerance (FI), more accumulated days to achieve total enteral nutrition, less accumulated days of total calories up to standard 110 kcal/kg/day and slower velocity of weight growth (P < 0.05 for all). Logistic regression analysis indicated that the maximum dose of amino acids (OR, 5.352; 95% CI, 2.355 to 12.161), EUGR (OR, 2.396; 95% CI, 1.255 to 4.572), FI (OR, 2.581; 95% CI, 1.395 to 4.775), surgically treated NEC (OR, 11.300; 95% CI, 2.127 ~ 60.035), and longer total hospital stay (OR, 1.030; 95% CI, 1.014 to 1.046) were independent risk factors for the development of PNAC. SMOF (OR, 0.358; 95% CI, 0.193 to 0.663) and breastfeeding (OR, 0.297; 95% CI, 0.157 to 0.559) were protective factors for PNAC. Conclusions PNAC can be reduced by optimizing the management of enteral and parenteral nutrition and reducing gastrointestinal comorbidities in preterm infants.